A Comparative Clinical Study to Evaluate the Effect of Vatari Guggulu and Shatpushpadi Churna with Simhanada Guggulu in the Management of Amavata w.s.r. to Rheumatoid Arthritis (AYUSHDHARA, 2023)
The disease Amavata described in classical Ayurvedic literature is closely resembles with Rheumatoid Arthritis (RA). Amavata is a crippling condition where simultaneously aggravated Vata and Ama associated with each other settles in Sandhis and produce Sandhishoola, Sandhishotha, Sparshaasahitwa, which is similar to Rheumatoid Arthritis. Amavata is the challenging problem for medical science with different treatment protocol. The objectives of this randomized parallel group Comparative study were to evaluate the effect of Vatari Guggulu and Shatpushpadi Churna with Simhanada Guggulu in the management of Amavata w.s.r. to Rheumatoid Arthritis This Study was conducted on 32 patients selected randomly from OPD and IPD of R.G.G.P.G. Ayurvedic College and Hospital, Paprola, Dist. Kangra (H.P.) and divided into 2 groups. Group I and Group II having 16 patients in each group. Group A were managed with Vatari Guggulu 500mg BD with lukewarm water and Shatpushpadi Churna 3gm BD with lukewarm water while Group B were managed with Simhanada Guggulu 500mg BD with lukewarm water for 6 weeks. Results showed statistically significant difference in effect of Group I and Group II on subjective parameters – Angamarda, Trishna, Apaka, Jadya, Sparsh Ashyata, Vidvibandha, Nidravipraya, ESR, walking time and grip strength. Percent wise Vatari Guggulu and Shatpushpadi Churna are found to be more effective than Simhanada Guggulu for all assessment criteria in the management of Amavata.